The Role of the Library and Information Services in Promoting National Security in Nigeria - Onuoha, Aruabuike Elijah; Olatunde, Comfort Olukemi; Usman, Khadijat Asabe (POMLIF Journal of Library and Information Science, 2021)
National Security is essential for the survival of Nigeria as a nation. The security situation in contemporary Nigeria is so volatile and terrifying that it seems that each new day comes new more security problems that are oftentimes beyond the control of individuals and as such pose significantly challenge to the civil society. This paper attempts to outline how library and information services can be employed to curb the rising scale of insecurity in the country. It also highlights the challenges being faced by library services in Nigeria. Recommendations were also made on how the library could be out in the right place to carry out its duty in reducing insecurity in the country.